Pengaruh Komunikasi, Motivasi dan Kepuasan Kerja terhadap Kinerja Karyawan (Studi pada Proyek Pondasi Tower di Timor Leste PT Cahaya Inspirasi Indonesia) - Purwanto, Sony Bagus (Jurnal Aplikasi Manajemen, 2013)
Interest: study aims to clarify whether the effect of communication directly or indirectly to theperformance through motivation and job satisfaction. Design/methodology/approach; types of survey researchinvolving 79 respondents representing 380 employees PT Cahaya Inspirasi Indonesia of the towerproject in Timor Leste period from 2010 to 2012. Research limitations: that the study is limited to the threeindependent variables, namely communication, motivation and job satisfaction, employees are afraid tosay the truth that they experience in the field, the respondent is limited to strata equitable education(elementary, junior high and high school). Originality/value: Testing a direct influence on the performanceof communication, the value of beta coefficient standardized the value 0.923 (positive) so it can be concludedthat the communication variables significantly influence the performance variables. Testing theindirect effect of communication on performance through motivation, obtained the data processing standardbeta coefficient on the value of 0.916 (positive) so it can be concluded that communication indirecteffect on performance through motivation. Testing the indirect effect of communication on performancethrough job satisfaction, obtained the data processing standard beta coefficient on the value of 0.918(positive) so it can be concluded that communication indirect effect on performance through job satisfaction.